Analysis of public responses to political controversies in the beauty industry: A case study of Rose All Day and Esqa Brand owners in support of Israel - Nazahra, Gusti Nadya (Gema Wiralodra, 2024)
On October 30, 2023, Indonesia's beauty industry was shocked by the boycott of two well-known local brands, ESQA and Rose All Day. The trigger for this boycott was the actions of the owners of the two brands, Angelina Cindy and Tiffany Danielle, who gave support to Israel by "liking" Gal Gadot's controversial post. The public response to this action led to disappointment and boycott from most Indonesian netizens. This research uses a qualitative method with a literature study approach. Analysis was conducted on the chronology of events, public responses on social media, and apologies from brand owners. The data was analyzed to understand the impact of individual actions in the context of social media and how public responses affect brand reputation. A simple action such as a "like" on social media by a brand owner can trigger a large public response and significantly affect brand reputation. Public responses to political controversies can result in product boycotts and create pressure on companies to take a stand. The brand owners, in this case Angelina Cindy and Tiffany Danielle, responded by apologizing and clarifying their stance on the Israeli-Palestinian conflict. This incident highlights the complexity of public response, the impact of individuals in the age of social media, and the need for dialog and education in dealing with sensitive issues.